'You play like a Woman!' Effects of gender stereotype threat on Women's performance in physical and sport activities: A meta-analysis. (November 2018) - Gentile, Ambra; Boca, Stefano; Giammusso, Isabella
Abstract: Objectives: The purpose of this quantitative review was to provide an estimation of the effect of stereotype threat on women's performance in sport. Design: This review employed a meta-analytic technique. Method: a meta-analysis with random effects model was performed on 24 effects. Publication bias was tested through funnel plots and Egger's regression test. Results: Findings show a symmetric distribution of effects, making it possible to conclude that no file-drawer problem affected the collected sample of effects. Aggregating the results of the reviewed studies, a medium effect of stereotype threat manipulation on women's sport performances emerged ( d = 0.33). Collected studies were coded for stereotypicality of threatened exercise. The effect of stereotype threat was significantly higher for sports activities perceived as masculine. Conclusions: This meta-analysis reveals that gender stereotype affects the sport activities of women and that this is particularly true for sports typically considered suited to males. Highlights: Stereotype threat affects sport performances of women. Women experience stereotype threat especially when the sport is typically masculine. Both cognitive overload hypothesis and explicit monitoring hypothesis are plausible in sensorimotor task.